Experimental observations of an n = 1 helical core accompanied by a saturated m/n = 2/1 tearing mode with low mode frequencies in JT-60U. (11th October 2019) - Bando, T; Matsunaga, G; Takechi, M; Isayama, A; Oyama, N; Inoue, S; Yoshida, M; Wakatsuki, T
Abstract: We report the experimental finding of n  = 1 helical cores (HCs) accompanied by saturated m / n  = 2/1 tearing modes (TMs) with low mode frequencies in JT-60U. The HCs accompanied by TMs were observed after an increase in the mode amplitude and a decrease in the mode frequency of m / n  = 2/1 precursors with tearing parity. The decreased mode frequency is typically lower than 20 Hz. With various diagnostics, the coupling of n  = 1 HCs and m / n  = 2/1 TMs has been clearly observed. Because the coherent oscillations in the ion temperature are observed in both the core region and the edge region, the flux surfaces including the m / n  = 2/1 magnetic island appear to have m  = 1 helical deformation. It has also been suggested that the m / n  = 2/1 TM and the HC rotate in the electron diamagnetic direction keeping f m / n =1/1(HC)  = 2 f m / n =2/1(TM) in several plasmas. Here, f m / n =1/1(HC) is the mode frequency of HCs and f m / n =2/1(TM) is the mode frequency of TMs. In addition, the core seems to be shifted to the high-field side when the O-points of the m / n  = 2/1 magnetic island line up in the midplane, which is confirmed by reconstructions of magnetohydrodynamic equilibria with motional Stark effect measurement and the MEUDAS code. Our observation of m / n  = 2/1 TMs having HCs contributes to the understanding of the excitation mechanism of HCs in tokamak plasmas.